Performance comparison of one &two quantum wells light emitting diodes simulated with COMSOL multiphysics - Kumar, P. (Institute of Electrical and Electronics Engineers Inc., 2017)
Light-emitting diodes are employed in numerous applications such as, displaying information, communications, sensing, illumination and lighting. In this paper, AlGaN/InGaN based two quantum wells (2QWs) light emitting diode (LED) is modeled and studied numerically using COMSOL Multiphysics. The electrical, electronic and optical parameters are extracted from the device. The performance of 2QWs LED is investigated by comparing device behavior with respect to available one quantum well (1QW) light emitting diode model. Very close turn-on voltage values are achieved for both LED models. A non-uniform emission is also found from 2QWsLED model along with high efficiency drooping. © 2016 IEEE.